Potensi dan Strategi Pengembangan Ekowisata Di Resort Konservasi Wilayah (RKW) III Taman Wisata Alam Ruteng, Desa Golo Loni,Kecamatan Ranamese, Kabupaten Manggarai Timur, Provinsi Nusa Tenggara Timur - Pasang, Gregoria Reina; Purnama, Maria M. E.; Sinaga, Pamona Silvia (Wana Lestari, 2022)
Ruteng Natural Tourism Park (TWA) is rich in natural resources with regional potential in the form of stunning panoramas, and a variety of local cultural wisdom that has the potential as a location for developing tourist destinations. However, the tourism potential of RKW III TWA Ruteng has not been managed properly due to the lack of promotional/marketing activities, then the unavailability of tour packages that are packaged attractively and globally, resulting in low visits, both local and foreign tourists. The aim is to determine the potential and assessment of tourist attractions from each of the existing criteria and to formulate an ecotourism development strategy. The tourism potential assessment uses the 2003 ADO-ODTWA guidelines from the Director General of PHKA and the development strategy uses a SWOT analysis looking at strengths, weaknesses, opportunities, and threats. The results show that the potential offered is the beauty of the panoramic attraction of Lake Ranamese, waterfalls of Lake Ranamese, and various types of beautiful flora and fauna. The results of the calculation of the feasibility of the RKW III TWA Ruteng tourist location based on the assessment criteria, namely attractiveness 81.1%, accessibility 98.3%, accommodation 75%, and facilities and infrastructure 100%. The total number of assessments from these 4 criteria is 89.85%, so it can be concluded that RKW III TWA Ruteng is worthy of being developed as a tourist location. Strategies that need to be carried out are promoting attractively packaged tour packages for students, researchers, family tours, repairing and adding damaged facilities and infrastructure, adding types of tourism activities, providing space for local community involvement in the development of ecotourism activities and designing collaborations with surrounding tourist sites.